2014
DOI: 10.1159/000355644
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Understanding the Impact of Technologies for Aging in Place: A Mini-Review

Abstract: Background: There are many approaches to evaluating aging-in-place technologies. While there are standard measures for outcomes such as health and caregiver burden, which lend themselves to statistical analysis, researchers have a harder time identifying why a particular information and communication technology (ICT) intervention worked (or not). Objective: The purpose of this paper is to review a variety of methods that can help answer these deeper questions of when people will utilize an ICT for aging in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…However, insight in the interplay and dynamics between factors is very limited. As noted by others, we still do not know very much about when, how and why community-dwelling older adults acquire technology [ 19 , 28 – 31 ]. Additionally, from both a healthcare and business perspective, the ultimate goal is to develop and deploy technologies that contribute to the quality of life of older adults [ 29 , 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, insight in the interplay and dynamics between factors is very limited. As noted by others, we still do not know very much about when, how and why community-dwelling older adults acquire technology [ 19 , 28 – 31 ]. Additionally, from both a healthcare and business perspective, the ultimate goal is to develop and deploy technologies that contribute to the quality of life of older adults [ 29 , 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Connelly et al have found that evaluation of ICTs for aging in place requires multiple methods because of the wide variety of nuanced contexts in which older adults live [3]. Lyles et al showed that lack of technical support and the fear of losing the doctorpatient relationship were barriers to adoption of patient portals for AfricanAmerican and Latino patients [4,5].…”
Section: Barriers To Adoption Of Patient Portalsmentioning
confidence: 99%
“…In this context, technologies for ageing in place (Pastalan, 1990;Connelly, Mokhtari and Falk, 2014;Normie, 2011) are important facilitators. This study is part of a medium-term project that aims to systematize current evidence of technologies for ageing in place (Queirós, Pereira, Dias and Rocha, 2017;Queirós, Pereira, Santos and Rocha, 2017;Queirós, Santos, Cerqueira and Rocha, 2017) and its main goal was to report technological solutions to support community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%